Causal Modelling of Participants Reaction in The Management Training - Ronny Kountur (Sinergi: Kajian Bisnis dan Manajemen, 2008)
This research was intended to find out variables that affect the reaction of participants attending management courses. It was hypothesized that participants reaction are affected by variables such as instructor, course material, participation during the session, and training supporting facilities. While the participation during the session were affected by instructor and course material. The relationship between these variables is a structural form and described by a causal modeling relationship. This causal relationship was tested for its significant using path analysis technique. Data were collected using questionnaires to the 120 participants that were attending management training. The validity and reliability of this instruments had been tested. It’s reliability was tested using Cronbach Alpha with a reliability of 86%, which are considered as reliable. It was found out that instructor and course material affected the satisfaction of participant while attending management training, however, negative relationship was found between instructor and course material. Both of these variables, instructor and course material, were also found to affect the participation during the session. The other two variables which are participation during the session and training supporting facilities were found to have no affect on both, participants reaction and participation during the session. Two aspects of instructor that were studied, the understandability in delivering the material and the attractiveness of the presentation. While, there were also two aspects of course material that were studied, the applicability of the material and the readability of the materials.Keywords: Model sebab-akibat, pelatihan manajemen, peserta, instruktur, materi